A New Setup for Real-Time Investigations of Optical Fiber Sensors Subjected to Gamma-Rays: Case Study on Long Period Gratings - Stancalie, Andrei (Sensors (Basel), 2020)
In this work, we present a new setup for real-time investigations of optical fibers and optical fiber sensors while being subjected to gamma-rays. The investigation of the radiation effects on novel or well-assessed sensing devices has attracted a lot of interest, however, the facilities required to do this (when available) are barely accessible to the device to be characterized. In order to reduce the limitations of these types of experiments and ensure a highly controlled environment, we implemented a configuration that permits the on-line testing of optical components inside a Co-60 gamma chamber research irradiator. To show the advantages of this new approach, we present a case study that compares an arc-induced optical fiber long period grating (LPG) irradiated in a gamma chamber with the same type of grating irradiated with gamma-rays from a Co-60 industrial irradiator. In order to better understand the effects of radiation on such components and their behavior in radiation environments, we focus on the homogeneity of the radiation field and parameter customizability as well as the high reproducibility of the experiments.